Resonancias del cuidado de enfermería en el proceso del buen morir de la persona con cáncer - Sánchez Andrade, Carmen Miriela (2020)
The objective of this qualitative study is to describe and comprehensively analyze the “Nursing Care Resonances in the Process of Good Death of the Person with Cancer” based on the theoretical basis of Leonardo Boff on humanized care; Watson and Waldow in the concepts of nursing care; death and process of good death according to Elizabeth Kübler-Ross. Twenty-two nurses who work in the Intensive Care, Emergency and Hospitalization Unit of the Regional Institute of Neoplastic Diseases in northern Trujillo participated, the in-depth interview and participant observation was used. Results emerged the category resonances of care with their respective subcategories: love as an ethical and biological phenomenon to be one with death; body caress, word and essential silence in care; overcome the porcupine effect with tenderness for transformational care; compassion without ego and body scan in the process of good death; cordiality, forgiveness and fundamental support in care. Conclusions: nurses demonstrate their strengths by applying more than one resonance of care, highlighting compassion and cordiality as the main categories that emerge in a reflective and critical spirit during care in the process of good death of the person with cancer.